'Wild Rivers, Wild Ideas': Emerging Political Ecologies of Cape York Wild Rivers. (October 2013) - Slater, Lisa
In 2005 the Australian Queensland state government passed the Wild Rivers Act to preserve the natural heritage of rivers. My interest is not with all Wild Rivers but rather with those in Cape York where the public debate has been fierce and divisive. Prominent Cape York Aboriginal leaders and organisations condemned the bill. A coalition of north Queensland Traditional Owners support the policy and call for the 'proper Indigenous management of country' and the right people to speak for country. The conflict is an example of the argument put forward by some scholars that Cape York politics is being reconfigured: there is a schism between regionally focused visions of Indigenous futures and locally focused traditionalist visions held by community leaders 'living on country'. Analysing the Wild Rivers debate in conjunction with Holmes's and Smith's findings, one is struck by the emerging political ecology: rivers are becoming political actors. By bringing the postcolonial into relation with more-than-human praxis, I want to prise open this debate to consider what the public controversy conceals, what political practices are emerging, and what this demands of scholarship. When rivers become political actors the concept and practice of social justice are potentially reconfigured. What happens when we take seriously rivers as actors in a multirealist world? We know that rivers sustain and reproduce life, but which life worlds are being considered?